Customer Satisfaction as a Mediator of the Influence of Taste, Packaging, and Price Perception on Repurchase Intention of Mixue in East Surabaya - Clarrisa Kurnia Fitriani; Siti Mujanah; Achmad Yanu Alif Fianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of taste, packaging, and price perception on repurchase intention with customer satisfaction as a mediating variable among Mixue consumers in East Surabaya. The research method used is quantitative with purposive sampling technique and involved 100 respondents who have made purchases more than three times. Data collection was carried out by distributing questionnaires that have been tested for validity and reliability. Data analysis used the Structural Equation Modeling (SEM) approach with the Partial Least Square (PLS) method through SmartPLS 3.9.9 software. The results showed that taste and price perception have a positive and significant effect on repurchase intention, while packaging has a positive but insignificant effect. Taste and price perception are also proven to have a positive and significant effect on customer satisfaction, while packaging again shows a positive but insignificant effect. In addition, customer satisfaction has a positive and significant effect on repurchase intention. The mediating role of customer satisfaction is proven to be significant in the relationship between taste and price perception on repurchase intention, but not significant in the relationship between packaging and repurchase intention. These findings indicate that product taste and perceived price to quality play a dominant role in increasing customer satisfaction and driving repeat purchase intentions among Mixue consumers.